Patterns of Pediatric Facial Fractures. Issue 4 (December 2021) - Hong, Kevin; Jeong, James; Susson, Yehudah N.; Abramowicz, Shelly
Objective: The aim of this study was to assess patterns of maxillofacial trauma in the pediatric population in Atlanta. This information is important to help guide management and allocate resources for treatment of maxillofacial injuries at Children's Healthcare of Atlanta (CHOA). Methods: This study was a retrospective chart review of children who presented from 2006 to 2015. Inclusion criteria were: (1) age 18 years old or younger, (2) presentation to emergency department, (3) diagnosis of maxillofacial fractures, and (4) evaluation by Oral and Maxillofacial Surgery, Otolaryngology, or Plastic Surgery services. Medical records were reviewed to record demographic, mechanism of injury, fracture location, and yearly incidence of injury. Descriptive statistics were computed to summarize findings and overall trends. Results: During the study period, 39, 833 patients were identified. Of them, 1995 met the inclusion criteria. The majority were male (n = 1359, 68%) with an average age of 9.4 years old (range of 1 month to 18 years old). Mechanisms of injury were motor vehicle collisions (MVC) (n = 597, 29.9%), fall (n = 565, 28.3%), sports injury (n = 317, 15.9%), pedestrian struck (n = 215, 10.8%), assault/abuse (n = 204, 10.2%), other (n = 81, 4.1%), or gunshot wound (n = 16, 0.8%). Fracture sites were mandible (n = 519, 26%), complex (n = 479, 24%), nasal (n = 419, 21%), dentoalveolar (n = 279, 14%), orbital (n = 259, 13%), and maxilla (n = 40, 2%). Males had a higher incidence of assault than females (n = 185, 91% of assaults). The incidence of maxillofacial trauma increased with age with a peak incidence in 13 to 16-year-olds (n = 566, 28.3%). During the years examined, there was an upward trend in MVCs as the etiology with a peak incidence of facial fractures due to MVCs occurring in 2015. All other mechanisms remained constant during this time period. Conclusions: There was an increase in pediatric facial fractures secondary to motor vehicle collisions from 2007 to 2015 despite improvements in regulations, traffic safety, and technology.